2019
DOI: 10.12765/cpos-2019-04
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Intentions and Views on Gender Roles: Russian Women in Estonia from an Origin-destination Perspective

Abstract: In this article we investigate fertility intentions of Russian women in Estonia from an origin-destination perspective. Russian migrants to Estonia and their descendants are compared with women in the sending and host countries in order to identify similarities and differences in intended transitions to first, second and third births. The study is based on the Estonian and Russian Generations and Gender Surveys, which were conducted in 2004/2005, and employs logistic regression models. The dependent variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Their results suggest that Russian migrants and their descendants in Estonia have fertility intentions more similar to those of their counterparts in Russia than to those of Estonians. Nevertheless, aspects strictly related to integration, such as language proficiency and having a native partner, are linked to higher chances of adopting typical host country fertility intention patterns among migrants and their descendants (Puur et al 2018). These findings indicate that cultural embeddedness matters in shaping fertility intentions.…”
Section: Fertility Intentions In the Short Termmentioning
confidence: 79%
See 2 more Smart Citations
“…Their results suggest that Russian migrants and their descendants in Estonia have fertility intentions more similar to those of their counterparts in Russia than to those of Estonians. Nevertheless, aspects strictly related to integration, such as language proficiency and having a native partner, are linked to higher chances of adopting typical host country fertility intention patterns among migrants and their descendants (Puur et al 2018). These findings indicate that cultural embeddedness matters in shaping fertility intentions.…”
Section: Fertility Intentions In the Short Termmentioning
confidence: 79%
“…The first generation instead shows more positive short-term fertility intentions compared to natives, while the 1.5 generation occupies an intermediate position (Carlsson 2018). Puur et al (2018) recently studied the fertility intentions of Russian migrants and their descendants in Estonia, comparing non-migrants in Estonia and Russia. Their results suggest that Russian migrants and their descendants in Estonia have fertility intentions more similar to those of their counterparts in Russia than to those of Estonians.…”
Section: Fertility Intentions In the Short Termmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey-based study that focussed on first-and second-generation Russians in Estonia, Puur et al (2017) showed that residence amongst the host population outside of areas with a high concentration of immigrants was associated with convergence of the Russians' third-birth risks with those of the host population. A related study found a similar association for the intentions of Russian women in Estonia to have another child (Puur et al 2018).…”
Section: Theoretical Perspectives and Previous Findingsmentioning
confidence: 56%
“…A large bulk of studies analyzed natives' fertility intentions (FIs, hereinafter) (Régnier-Loilier and Vignoli, 2011;Balbo and Mills, 2011;Gatta et al, 2021;Novelli et al, 2021) and literature on migrants' FIs grown significantly in recent years (Kraus and Castro-Martín, 2018;Puur et al, 2018;Carlsson, 2018;Alderotti et al, 2022-forthcoming). However, to the best of our knowledge, none of the former investigated the role that the combination of partners' nationalities may play in individual's intentions to have a(another) child.…”
Section: Introductionmentioning
confidence: 99%